Rendeiras da Vila de Ponta Negra Natal/RN: o ensino da renda de bilro e do desenho como alternativa de continuidade da produção artesanal tradicional - Cordeiro, Angela Dias (2010)
This paper analyzes the development of Bobbin Lace and Design workshops, in the neighborhood of Vila de Ponta Negra (in Natal - RN, Brazil), which proposed contents and practices for its learning and teaching that would compose a possible model for a hybrid Workshop of Bobbin Lace and Lace Design. This research was based on Ergonomic Work Analysis, a methodology used by Ergonomics to analyze work in a wide approach, considering cognitive, social, organizational, as well as other aspects which are relevant to the study of the working situation, in terms of learning/teaching, as addressed on this paper. Some steps of the above mentioned methodology were followed in order to understand the activity of Bobbin Lace craftswomen, by means of bibliographical research centered on this activity. The instruments used for collecting data comprise of conversational actions, analysis of collective work, and spontaneous as well as provoked verbalizations. The adaptations performed in the process of learning/teaching Bobbin Lace for the achievement of Bobbin Lace and Design workshops became instrumental for the continuity of that tradition, attracting new apprentices to this art/craft causing to revitalize a network of handicraft economical activities linked to the Bobbin Lace production, such as the making of cushion, bobbins and trestles